Development and testing of a manual operated coconut milk extractor - AJINAS BASHEER T MIDHILA LEKSHMI S NIDHIN J.K; Dr. Jayan P.R (Guide) (Tavanur 2015 DEPARTMENT OF FARM POWER MACHINERY AND ENERGY)
Development and testing of a manual operated coconut milk extractor
Development and testing of a manual operated coconut milk extractor